Zur Visualisierung des Satzes von Pythagoras - Giering, Oswald (Teaching Mathematics and Computer Science, 2009)
In this article we make a study of a not-classical visualization of the theorem of Pythagoras using methods of elementary school geometry. We find collinear points, copoint straight lines and congruent pairs of parallelograms. The configuration of their midpoints induces a six-midpoint and a four-midpoint theorem.